American engineering troops in the Vietnam conflict of 1964–1975 - Pietrygała, Robert; Cutter, Zdzisław (Armia kontra natura, 2020)
The article focuses on the period of the Vietnam War, with particular emphasis on the role played by engineering troops (as a necessary component of individual tactical associations, and a guarantee of success of military operations conducted by the US army). The paper presents the engineering troops’ efforts to build military infrastructure, as well as the assistance provided to the South Vietnamese society. The article contains a list of all engineering units of the American army involved in the Vietnamese conflict, their organizational structure, personnel status, dislocation, as well as the scope of tasks assigned to them. In addition, it shows the cooperation between engineering units and civil contractors at the service of the army (especially in the period preceding the direct involvement of the United States in the war).